2005
DOI: 10.1007/bf02893857
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of tumor markers for differentiating malignant and benign pleural effusions of Iranian patients

Abstract: In order to evaluate the diagnostic yield of tumor markers in differentiating malignant and benign pleural effusions, we carried out a prospective study in a group of Iranian people. Pleural and serum levels of carcinoembryonic antigen (CEA), carbohydrate antigen 15-3 (CA 15-3), neuron-specific enolase (NSE) and cancer antigen 125 (CA 125) were assayed prospectively in patients with pleural effusion (40 malignant and 37 benign). The highest sensitivity was obtained with a combination of CA 15-3 in serum, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Furthermore, in agreement with other authors (12,20), Ca125 is not recommended as a useful diagnostic tool in malignant pleural effusion since immunohistochemical studies have shown that Ca125 is released from the pleura as well as from the peritoneum. In the present study, when the percentage of positivity for Ca125 was considered in the cytosolic materials of pleural effusion sediments, no significant difference was observed between benign and malignant diseases.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, in agreement with other authors (12,20), Ca125 is not recommended as a useful diagnostic tool in malignant pleural effusion since immunohistochemical studies have shown that Ca125 is released from the pleura as well as from the peritoneum. In the present study, when the percentage of positivity for Ca125 was considered in the cytosolic materials of pleural effusion sediments, no significant difference was observed between benign and malignant diseases.…”
Section: Discussionsupporting
confidence: 83%
“…Diagnosis is normally carried out by invasive techniques, such as thoracoscopy, which show sensitivity but are not costeffective and induce physical and mental stress in the patient (8). The role of biochemical parameters or tumour markers were previously studied in order to increase the diagnostic capacity of pleural effusion analysis (9)(10)(11)(12)(13). The detection of these parameters or markers in bodily fluids is the result of a dynamic balance between the number of cells that synthesize the tumour marker, its capacity for synthesis and the amount eliminated by the organism relative to the nature, size and metabolic mechanism of the marker.…”
Section: Introductionmentioning
confidence: 99%
“…A malignant pleural effusion may be the initial presentation of cancer in 10 to 50% of patients [2]. The cytologic diagnosis of pleural effusions can be difficult and usually detect only 50–60% of malignant pleural effusions [3], especially in specimens containing abundant reactive mesothelial cells. Distinguishing carcinoma cells from reactive mesothelial cells in such fluid are particularly challenging when there are relatively few carcinoma cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…CA125 is released from the pleura as well as the peritoneum and the positivity of this marker was recognized in the cytosolic materials of pleural effusion sediments and no significant difference was observed between benign and malignant diseases (13). Based on the previous reports (14,15), CA125 is not recommended as a useful diagnostic tool in MPE. In present study, serum CA125 level was significantly higher in the patients with occult MPD, although there was no significant difference by the multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%